2022
DOI: 10.26442/00403660.2022.03.201412
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory diseases and obesity: special phenotype or independent events: Review

Abstract: A combination of factors, including Western European eating habits, physical inactivity and genetic predisposition, lead to a dramatic increase in adipose tissue mass. A special place is occupied by abdominal obesity, in which there is an accumulation of adipose tissue in the mesentery of the small intestine and the omentum. Developing in conditions of visceral obesity, insulin resistance, dyslipidemia and systemic inflammation are one of the key components of the pathogenesis of type 2 diabetes mellitus, card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 92 publications
0
1
0
1
Order By: Relevance
“…Recent literature has shown that obesity is associated with impaired pulmonary function and increased risk of respiratory diseases [6,[10][11][12][13][14][15][16][17][18][19][20][21]. Bantula et al and Zammit et al indicated that asthmatic patients with obesity have severe disease, need intense treatment, harder to treat and have frequent acute attacks [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature has shown that obesity is associated with impaired pulmonary function and increased risk of respiratory diseases [6,[10][11][12][13][14][15][16][17][18][19][20][21]. Bantula et al and Zammit et al indicated that asthmatic patients with obesity have severe disease, need intense treatment, harder to treat and have frequent acute attacks [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Ожирение оказывает существенное влияние на биомеханику дыхания: увеличение массы жировой ткани в брюшной и грудной полости повышает внутрибрюшное и плевральное давление, что приводит к изменению геометрии диафрагмы и усиленной работе дыхательных мышц в энергетически невыгодных условиях, следствием чего является их утомляемость [4]. Отложение жировой ткани вокруг ребер и в средостении ограничивает подвижность грудной клетки, препятствует расправлению легких на вдохе и спадению их на выдохе.…”
unclassified